(untitled) (Comprehensive Journal of Science, 2026)
This research aims to analyze the role of school administration in fostering creative thinking among basic education teachers in light of constructivist theory, within the context of contemporary educational transformations that emphasize innovative and supportive school leadership as a key factor in improving educational quality. The study employed a systematic thematic analysis to review 30 peer-reviewed studies published between 2019 and 2025, retrieved from specialized Arabic and international academic databases using clearly defined inclusion and exclusion criteria. The data were analyzed following Braun and Clarke’s thematic analysis framework through methodological, theoretical, and contextual (Arabic and international) classifications, focusing on leadership styles, organizational climate, professional development programs, and their relationship to teachers’ creative thinking. The findings revealed a strong positive relationship between supportive administrative practices, creative school leadership, and the development of creative thinking among teachers. The results also highlighted the significance of adopting constructivist principles based on interaction, active learning, and knowledge construction in enhancing creative teaching practices. However, the review identified notable methodological gaps, particularly the scarcity of longitudinal and experimental studies and the limited focus on basic education teachers in some Arabic contexts. The study recommends promoting creative leadership models in schools, designing constructivist-based professional development programs, and encouraging intervention-based research to enhance teachers’ creative thinking.